Warring souls : youth, media, and martyrdom in post-revolution Iran - Varzi, Roxanne, 1971- (E-Duke books scholarly collection., 2006)
An ethnography of secular youth culture in Tehran and its resistance to post-Revolutionary Islamicist politics.